2009
DOI: 10.5539/ijbm.v4n12p153
|View full text |Cite
|
Sign up to set email alerts
|

The FDI- Led- Growth Hypothesis in ASEAN- 5 Countries: Evidence from Cointegrated Panel Analysis

Abstract: The paper works out the relationship between foreign direct investment (FDI) and economic growth in the five ASEAN countries namely, namely Indonesia, Malaysia, Philippines, Singapore and Thailand over the period . The empirical analysis is based on cointegration and causality test, both at the individual level and panel level. The results confirm that foreign direct investment and economic growth are cointegrated at the panel level, indicating the presence of long run equilibrium relationship between them. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 43 publications
1
22
0
5
Order By: Relevance
“…. By making use of data for the period 1975-2009, Soltani and Ochi (2012 considered the causal relationship between FDI and economic growth in Tunisia. In addition, the twoway linkage between FDI inflows and economic growth in which FDI involves economic growth and, in turn, economic growth is viewed as a tool to attract FDI has not yet been studied.…”
Section: Fdi Inflows and Economic Growth : A Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…. By making use of data for the period 1975-2009, Soltani and Ochi (2012 considered the causal relationship between FDI and economic growth in Tunisia. In addition, the twoway linkage between FDI inflows and economic growth in which FDI involves economic growth and, in turn, economic growth is viewed as a tool to attract FDI has not yet been studied.…”
Section: Fdi Inflows and Economic Growth : A Synthesismentioning
confidence: 99%
“…Such research has shown that the accumulation of foreign capital is one of the main determinants of economic growth 2 . Some empirical studies confirm positive economic growth from FDI inflows (e.g., Borensztein et al, 1998 ;2008;Chakrabarti, 2001;Schiff and Wang, 2008), but others find negative or no impacts (e.g., Duasa, 2007 ;Pradhan, 2009). In the case of the three selected countries, studies focus on analyzing the linkage between FDI inflows and economic growth are limited (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Örneğin Basu vd. (2003), Choe (2003), Hsiao ve Hsiao (2006), Pradhan (2009), Ericsson ve Irandoust (2010), Mah (2010), Abbes vd. (2015) çalışmalarında doğrudan yabancı yatırımlar ve ekonomik büyüme ilişkisi; Gastanaga vd.…”
Section: Introductionunclassified
“…All these factors are believed to be partly responsible for the country's economic development and growth. FDI are significant, not only to the developing nations like Rwanda, as well as the developed countries (Pradhan, 2009) [3].…”
mentioning
confidence: 99%